On-Column Ion-Exchange Preconcentration of Inorganic Anions in Open Tubular Capillary Electrochromatography with Elution Using Transient-Isotachophoretic Gradients. 3. Implementation and Method Development - Michael Breadmore; Palmer, AS; Curran, MAJ; Miroslav Macka; Avdalovic, N; Paul Haddad (2002)
A solid-phase extraction method based on an ionexchange retention mechanism has been used for in-line preconcentration of inorganic anions prior to their separation by capillary electrophoresis (CE). A single capillary containing a preconcentration and a separation zone has been used in a commercial CE instrument without instrumental modification. Analyte anions were retained on a preconcentration zone comprising an adsorbed layer of cationic latex particles, while separation was achieved in a separation zone comprising fused silica modified by adsorption of a cationic polymer. Elution of the adsorbed analytes was achieved using an eluotropic gradient formed by a transient isotachophoretic boundary between a fluoride electrolyte and a naphthalenedisulfonate electrolyte. Optimization of the electrolyte concentrations, sample injection times, and back-flushing times allowed the successful separation of sub-ppb levels of inorganic anions using a 100-min injection at 2 bar pressure, introducing over 40 capillary volumes of sample. A method based on a 10-min injection allowed a 100-fold increase in sensitivity over conventional hydrodynamic injection for Br-, I-, NO3 -, CrO4 2-, and MoO4 2- with a total analysis time of 25 min. Detection limits were dependent on the injection time but were in the range 2.2-11.6 ppb for a 10-min injection time. This approach was used to determine NO3 - in Antarctic ice cores where the analysis could be performed using a sample volume 100 times less than that used for ion chromatography.